2002
DOI: 10.1079/phn2002357
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the second version of a quantitative food-frequency questionnaire for use in Western Mali

Abstract: Objective: To assess the relative validity of the second version of a quantitative foodfrequency questionnaire (QFFQ), designed to measure the habitual food and nutrient intake in one season in rural populations in Western Mali, West Africa. Design: The dietary intake during the previous week was assessed with the 164-item QFFQ administered by interview. This was compared with the intake from a 2-day weighed record (WR) with weighed recipes. Setting: The village of Ouassala in the Kayes region, Western Mali. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 34 publications
3
40
1
3
Order By: Relevance
“…The larger discrepancies in the index scores between the WRs and FFQ for women than for men confirm results from the two earlier validation studies (Torheim et al, 2001;Parr et al, 2002). Both studies concluded that the questionnaire Table 5 Crossclassification of subjects in quartiles (Q) of food variety score (FVS), diet diversity score (DDS) and mean adequacy ratio (MAR) from the food frequency questionnaire (FFQ) and from the weighed records (WR).…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…The larger discrepancies in the index scores between the WRs and FFQ for women than for men confirm results from the two earlier validation studies (Torheim et al, 2001;Parr et al, 2002). Both studies concluded that the questionnaire Table 5 Crossclassification of subjects in quartiles (Q) of food variety score (FVS), diet diversity score (DDS) and mean adequacy ratio (MAR) from the food frequency questionnaire (FFQ) and from the weighed records (WR).…”
Section: Discussionsupporting
confidence: 67%
“…The two earlier validation studies published on the FFQ (Torheim et al, 2001;Parr et al, 2002) compared intake of foods and nutrients from the FFQ and the WR, and median Spearman's correlation coefficient was in the range of 0.3-0.4 for both foods and nutrients. Correct classification was in the order of 29-36% (median values), while median gross misclassification ranged from 4 to 7%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations